2016
DOI: 10.1080/09593985.2016.1203046
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a smartphone pulse rate application for the assessment of resting and elevated pulse rate

Abstract: The Azumio® Instant Heart Rate application when used by either platform appears to be a reliable and valid tool to assess pulse rate in healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 14 publications
2
25
0
1
Order By: Relevance
“…On the other hand, another study used the intraclass correlation coefficient (Icc) to determine the validity of measurements before and after climbing stairs. the results showed a high degree of concurrent valid ity with the Polar ® device (Icc > 0.90) for the measures pre and postexercise, but there was no assessment during exercise [19].…”
Section: Introductionmentioning
confidence: 86%
“…On the other hand, another study used the intraclass correlation coefficient (Icc) to determine the validity of measurements before and after climbing stairs. the results showed a high degree of concurrent valid ity with the Polar ® device (Icc > 0.90) for the measures pre and postexercise, but there was no assessment during exercise [19].…”
Section: Introductionmentioning
confidence: 86%
“…HR-PPG measurements were obtained using the Instant Heart Rate app (Azumio inc), a popular application for measuring HR and a smartphone’s (any Apple© model or Android© phone model) camera and light. 38 PPG recordings are obtained “on demand” by the user steadily applying the pulp of their finger on the smartphone camera and thus is an on-demand measurement, as opposed to passive measurements made by some wearables. Participants were free to measure HR at any frequency and time of day.…”
Section: Methodsmentioning
confidence: 99%
“…Yan et al presented similar findings, although the correlations between the facial PPG–estimated HR and ECG HR had smaller variations ( r =.997 on resting compared with r =.982 with postmoderate intensity exercise) [59]. Furthermore, it was also found that both iOS and Android operating systems, with the same HR app, had concurrent validity with an FT7 Polar HR monitor at rest and at postexercise time points [60]. Although many studies reported the use of mobile phones as the media for measuring and interpreting HRs, some studies used mobile phone apps as a feedback system rather than the actual HR sensor.…”
Section: Resultsmentioning
confidence: 85%